Multi‐decadal morpho‐sedimentary dynamics of the largest Changjiang estuarine marginal shoal: Causes and implications. (6th August 2019) - Wei, Wen; Dai, Zhijun; Mei, Xuefei; Gao, Shu; Liu, J. Paul
Abstract: Understanding the long‐term evolution of estuarine shoals given natural variations and human modifications is a key issue for wetland protection and shoal management. Here, the multi‐decadal (1958–2013) morpho‐sedimentary dynamics of the Nanhui Shoal (NHS), the largest Changjiang estuarine marginal shoal, are studied using a suite of hydrological, sedimentological, and bathymetric data. The results show that the tidal flow regime and sedimentary mode around the NHS changed slightly after the 1980s. Moreover, the NHS experienced a siltation‐induced volume increase of 4.1 × 10 8  m 3, concentrated in the landward region, and seaward progradation, producing an increase in gross area of 33 km 2, during 1958–2013. Even so, the actual tidal flat resource decreased by 29% due to the reclamation of 202 km 2 . Transition in the development of the NHS is detected: a planar geometry transformation from a triangular cusp to an arcuate cusp during 1958–1989; vertical siltation in the landward region under a stable arcuate‐shaped geometry thereafter. Furthermore, a steeply sloping profile with grades of 2–11‰ formed in the northern section, which limits future reclamation to 80 km 2 there. Estuarine regime adjustment, inducing hydrodynamic alterations in the South Passage, dominated the geometric changes in the NHS during 1958–1989, whereas substantial siltation promotion projects led to the landward siltation after 1989. The decrease in sediment input downstream of the Three Gorges Dam has played a minor role in the shoal evolution. This work provides new insights into the long‐term morpho‐sedimentary responses of estuarine shoals to natural and artificial forcings and their implications for shoal exploitation.